IMMIGRATION POLICIES OF THE EUROPEAN UNION AFTER THE ARAB SPRING - YILMAZ, Eren Alper (SSD Journal, 2021)
The civil war and immigration problem, which were seen in many Arabian countries after the Arab Spring that created a domino effect in the Middle East, have a serious role in today’s international arena. The borders of the European Union were heavily affected by the results of these mass migration movements. In this process, due to the influx of Syrians to the European borders, the European Union has begun to follow more cautious policies against immigration; also the idea of “Fortress Europe”, which means isolating Europe from the strangers coming from outside of Europe, has started to be implemented more frequent since 2015 that the migration movements started to increase. In this process, the European Union has aimed to take control of the refugee crisis and to keep itself out of this crisis by focusing on quota criteria, barbed wire, readmission agreements and struggle with irregular migrants. The study is supposed to point out the migration policies of the EU after the Arab Spring and to be contributed to the literature in terms of understanding the humanitarian dimension of the EU’s approach to the refugee crisis.